2000
DOI: 10.1177/0095798400026002001
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Cultureand Gender-Specific Intervention for Increasing Resiliency among African American Preadolescent Females

Abstract: The purpose of this study was to assess the impact of an intervention on strengthening resiliency among African American preadolescent girls using a relational and Africentric focus. The hypotheses were that significant increases in Africentric values, ethnic identity, gender role beliefs, and self-concept would follow participation in the intervention. The target population was African American girls aged 10 to 12 years considered at risk based on socioeconomic context. Fifty-five girls were in the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
60
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 22 publications
7
60
1
Order By: Relevance
“…Although research is limited, some studies suggest that Blacks in general, may be less likely to experience poor mental health than Whites (Adams, 1999;Belgrave et al, 2000;McKelvey & McKenry, 2000;Pickett et al, 1993). For example, Black parents of mentally ill children had higher feelings of self-worth and lower levels of depression than White parents (Pickett et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although research is limited, some studies suggest that Blacks in general, may be less likely to experience poor mental health than Whites (Adams, 1999;Belgrave et al, 2000;McKelvey & McKenry, 2000;Pickett et al, 1993). For example, Black parents of mentally ill children had higher feelings of self-worth and lower levels of depression than White parents (Pickett et al, 1993).…”
mentioning
confidence: 99%
“…Additionally, Black women also reported significantly more support from family members, and they interacted more often with family members, than did White women. Other studies have directly linked family support with psychological well-being in Blacks (Adams, 1999;Belgrave et al, 2000;Coley & Beckett, 1988;Maton et al, 1996;McKelvey & McKenry, 2000;Pickett et al, 1993). For example, using a college sample, Jung and Khalsa (1989) found that perceived family support and ethnicity was related to lower levels of depression in Blacks.…”
mentioning
confidence: 99%
“…In another study, a relational and Africentric-focused intervention was assessed as it related to promoting resiliency in preadolescent African American females (Belgrave, Chase-Vaughn, Gray, Addison & Cherry, 2000). The intervention was aimed to increase self esteem, ethnic identity and Africentric values specifically in girls over a four month period.…”
Section: Culture and Resiliencementioning
confidence: 99%
“…The pretest analysis showed no differences in demographics between those participants who left and those who remained in the study. Africentric values were based on the seven principles of Nguzo Saba, which are: unity, self-determination, collective work and responsibility, cooperative economics, purpose, creativity, and faith (Belgrave et al, 2000). At the end of the intervention period, the girls who received the intervention scored higher on measures of Africentric values and ethnic identity.…”
Section: Culture and Resiliencementioning
confidence: 99%
See 1 more Smart Citation